pleas solve this poblem

Asked by  | 5th Aug, 2008, 12:54: PM

Expert Answer:

in the place x,  the question written as n 2      

     the question should be   ( 1 + m2) x2 + 2mcx  + ( c2 - a2)= 0 

 the 2 roots are equal  ( given )

 so the condition  is  b- 4ac = 0  ==>  b2 == 4ac

                                  (2 mc)2 ==4 ( 1+m2) ( c2 - a2)

                                 4 m2 c 2  ==4[ c2 +m2c2 -a2 - m2a2]  ===>c2    = a2 ( 1 + m2)

 therefore c2  == a2 ( 1 + m2)

Answered by  | 5th Aug, 2008, 05:30: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.